Microcomputer theory and servicing - Asser, Stuart M. (Prentice Hall, 1997)
Written by a team of seasoned computer-service professionals, this book provides unique single-source, in-depth coverage of all the important need-to-know topics related to digital fundamentals, microprocessor theory, and personal computer servicing--all within a balanced hardware/soft ware approach. Tech tips and Troubleshooting sections are highlighted in each chapter. Part I presents the fundamental concepts of real-world considerations of digital logic circuits; Part II introduces the microprocessor and its support devices using the Intel 8088/8086 microprocessor family; Part III discusses the theory of operation and servicing of various components that together from the microcomputer system; Part IV describes the skills and tools necessary for the set-up, installation, and servicing of a microcomputer system, with an emphasis on customer relations, diagnostics, and troubleshooting. For Microcomputer Repair and Computer Servicing Technicians.